ANALISIS PEMBIAYAAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Muhammad Nasir; Tasdik Ilhamudin; Rasyidusman Hannamara Furqan Nur (Politeknik Negeri Lhokseumawe, 2020)
Abstract: This study aims to analyze the effect of Islamic finance on economic growth in Indonesia. This study was conducted in 33 provinces with 7 years from 2011-2017. The research model uses panel data model. Financing Research Results provided by Islamic Commercial Banks are very useful in supporting economic growth. Research shows that most Indonesian provinces are still in quadrants II, III and IV. There is enough evidence that finance can spur economic growth. The recommendations of this study are that the government and related agencies focus on increasing funding in an effort to grow a higher economy in addition to the need to increase investment financing.Keywords: Financing, Economic Growth, and Panel Data